2017
DOI: 10.3390/ijms18071394
|View full text |Cite
|
Sign up to set email alerts
|

The Novel HDAC8 Inhibitor WK2-16 Attenuates Lipopolysaccharide-Activated Matrix Metalloproteinase-9 Expression in Human Monocytic Cells and Improves Hypercytokinemia In Vivo

Abstract: Dysregulated human monocytes/macrophages can synthesize and secrete matrix metalloproteinases (MMPs), which play important roles in the progression of sepsis. In this study, we investigated the effects and mechanism of a novel histone deacetylase (HDAC8) inhibitor, (E)-N-hydroxy-4-methoxy-2-(biphenyl-4-yl)cinnamide (WK2-16), on MMP-9 production and activation in stimulated human monocytic THP-1 cells. Our results demonstrated that the acetylation level of structural maintenance of chromosomes 3 (SMC3) was up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…Our results showed no effect of compounds 17, 8, and CA on the IκBα levels and MAPKs activity, see Figure 6. Similar effects were also referred for a synthetic derivative of CA, WK2-16 ((E)-N-hydroxy-4-methoxy-2-(biphenyl-4-yl)cinnamide) [34,40]. It was proposed that WK2-16 could influence transcription factors YY-1 and STAT-1/-3.…”
Section: Nf-b Activity [% Of Dmso]supporting
confidence: 53%
See 1 more Smart Citation
“…Our results showed no effect of compounds 17, 8, and CA on the IκBα levels and MAPKs activity, see Figure 6. Similar effects were also referred for a synthetic derivative of CA, WK2-16 ((E)-N-hydroxy-4-methoxy-2-(biphenyl-4-yl)cinnamide) [34,40]. It was proposed that WK2-16 could influence transcription factors YY-1 and STAT-1/-3.…”
Section: Nf-b Activity [% Of Dmso]supporting
confidence: 53%
“…Cinnamic acid alone and several CA derivatives demonstrated the ability to influence the activity or expression of the pro-inflammatory transcription factor NF-κB in previous studies [15,33]. The effect of N-arylcinnamamide derivatives with the modified cinnamyl phenyl ring on NF-κB activity was studied by Chen et al [23] as well as by Jan et al [34], but the effect of derivatives with the unchanged cinnamyl moiety is described here for the first time. Apart from compounds 1 and 4, all anilides were able to significantly attenuate the lipopolysaccharide (LPS)-induced NF-κB activation by 10% to 27% in the non-toxic concentrations of 2 and 0.5 µM (used for compounds 10 (R = 3,4-Cl), 11 (R = 3,5-Cl), 13 (R = 3,5-CF 3 ) with the lowest cell viability), see Figure 3.…”
Section: Inhibition Of Nf-κb Activity and Cell Signaling In Vitromentioning
confidence: 76%
“…Specific blockade of HDAC8 inhibited the release of proinflammatory cytokines, such as TNF-α and IL-1β, from monocytes in response to LPS in vitro and in vivo [19]. Our previous study revealed that a novel HDAC8 inhibitor, ( E )-N-hydroxy-4-methoxy-2-(biphenyl-4-yl)cinnamide (WK2-16), attenuated the production of inflammatory mediators, such as matrix metalloproteinases (MMPs) and IL-6, in monocytic THP-1 cells and decreased serum TNF-α and IL-6 levels in an endotoxemic mouse model [20]. Therefore, HDAC8 inhibitors may be therapeutic in the treatment of neuroinflammation-mediated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…NO #88-7346-88 TNF-α, #88-7066-2 IL-6, and #88-7010-88 IL-1β, eBioscience; San Diego, CA, USA). The quantitative levels of the cytokines were analyzed as previously described [58].…”
Section: Methodsmentioning
confidence: 99%